THE EFFECT OF FLASH CARD MEDIA USE ON EARLY CHILDREN'S NUMERIC ABILITY AT NURUL AMIN PARAMAYAN PAUD, SERANG REGENCY - Rena; Yolanda Pahrul; Moh.Bayi Tabrani; Inten Risna; Beni Junedi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to determine the effect of using Flash Card media on early childhood numeracy skills at PAUD Nurul Amin, Pamarayan District, Serang Regency, Banten. The background of this research highlights the importance of appropriate stimulation in developing children's cognitive abilities during the golden age. A quantitative method with a one-group pretest-posttest design was employed. The sample consisted of one experimental group that received treatment using Flash Card media. Data were collected through observation and documentation. The analysis results showed a significant improvement in children's numeracy skills after the treatment. Children demonstrated enhanced ability in answering questions and providing accurate responses. Based on these findings, it can be concluded that Flash Card media has a positive and significant impact on the numeracy skills of early childhood learners. Therefore, this media is recommended as an engaging and effective alternative for learning in early childhood education settings